Rancang Bangun Prototipe Heat Exchanger Type Shell and Tube Arah Aliran Searah - Azmain N Hatuwe; Anisa Muhammad Hayoto; Kristofol Waas (Department of Mechanical Engineering, 2025)
This research aims to analyze the design and fabrication of a parallel-flow shell-and-tube heat exchanger prototype. The research was motivated by the need for concrete and effective practical learning media in the Mechanical Engineering Department of Ambon State Polytechnic, which is currently limited to theoretical material. The design method for this device uses a